Sudden Cardiac Death in Hypertensive Patients. Issue 5 (May 2019) - Verdecchia, Paolo; Angeli, Fabio; Cavallini, Claudio; Aita, Adolfo; Turturiello, Dario; De Fano, Michelantonio; Reboldi, Gianpaolo
Abstract : In patients with hypertension, but without established cardiovascular disease, predictive factors for sudden cardiac death (SCD) remain undefined. We followed for an average of 10.3 years a cohort of 3242 initially untreated hypertensive patients without evidence of coronary or cerebrovascular heart disease at entry. All patients underwent a complete clinical examination which included ECG and 24-hour ambulatory blood pressure monitoring. At entry, the mean age of patients was 50.0 years, 45% were women, and 6.1% had type 2 diabetes mellitus. Average office blood pressure was 154/96 mm Hg, and average 24-hour ambulatory blood pressure was 136/86 mm Hg. Prevalence of left ventricular hypertrophy at ECG was 13.9%. During follow-up, SCD occurred in 33 patients at a rate of 0.10 per 100 patient-years (95% CI, 0.07–0.14). The rate of SCD was 0.07 and 0.30 per 100 patient-years, respectively, in the cohort of patients without and with ECG left ventricular hypertrophy ( P <0.01). In a multivariable Cox model with Firth penalized maximum bias reduction method for rare outcome events, left ventricular hypertrophy almost tripled the risk of SCD (adjusted hazard ratio, 2.99; 95% CI, 1.47–6.09; P =0.002) after adjustment for age ( P <0.0001), sex ( P =0.019), diabetes mellitus ( P <0.0001), and 24-hour ambulatory pulse pressure ( P =0.036). For each 10 mm Hg increase in 24-hour ambulatory pulse pressure, the risk of SCD increased by 35%. The time-dependent area under the receiver operating characteristic curve was 0.85 (95% CI, 0.74–0.96). We conclude that in patients with hypertension without established cardiovascular disease, age, diabetes mellitus, ECG left ventricular hypertrophy, and 24-hour ambulatory pulse pressure are independent prognostic markers for SCD in the long-term.